Optimization of HPMC Concentration in Psidium guajava Leaf Extract Floating Tablets - Nurafni Annisa Achmad; Ardiansyah Jumaedi Nasir; Amriani Sapra; Nur Khairi; Nurul Ulfah Ali (Journal of Experimental and Clinical Pharmacy (JECP), 2026)
Psidium guajava L. leaves have been empirically used in traditional medicine due to their flavonoid content, which exhibits antibacterial and anti-ulcer activities. A floating drug delivery system is intended to prolong gastric residence time and thereby enhance therapeutic effectiveness in the treatment of gastric ulcers. This study aimed to investigate the effect of varying concentrations of hydroxypropyl methylcellulose (HPMC) on the physical characteristics of floating tablets containing Psidium guajava leaf extract. The leaf extract, at a dose of 350 mg, was formulated into floating tablets using three HPMC concentrations: 10% (F1), 20% (F2), and 30% (F3). The tablets were evaluated for weight uniformity, hardness, friability, disintegration time, and floating properties. The results showed that all formulations complied with pharmacopeial requirements for weight uniformity, hardness (10-20 kg), friability (<1%), and disintegration time (<60 min). However, formulation F1 exhibited a longer floating lag time of 7200 s and failed to meet the floating ability criterion. Increasing HPMC concentration significantly affected tablet hardness, friability, and floating properties (p < 0.05). Formulation F2 demonstrated the most favorable characteristics, with hardness of 10.61 kg, friability of 0.69%, floating lag time of 60 s, and floating duration >12 h. In conclusion, HPMC concentration significantly influenced the physical and floating properties of Psidium guajava leaf extract floating tablets, with a 20% HPMC concentration providing the most optimal formulation characteristics.